Mindfulness-Based Interventions for the Improvement of Well-Being in People With Multiple Sclerosis: A Systematic Review and Meta-Analysis. Issue 6 (July 2020) - Carletto, Sara; Cavalera, Cesare; Sadowski, Isabel; Rovaris, Marco; Borghi, Martina; Khoury, Bassam; Ostacoli, Luca; Pagnini, Francesco
ABSTRACT: Objective: The study aims to meta-analytically review studies about the effects of mindfulness-based interventions (MBIs) on well-being of people with multiple sclerosis (MS). Methods: Seven electronic databases were searched from June 2018 to September 2018. A systematic review and a meta-analysis were conducted. Results: Twenty-one studies were included in qualitative synthesis, and 10 studies were included in meta-analysis. MBIs are effective with an overall moderate effect size (Hedges' g = 0.70) in improving well-being in people with MS, with lasting effects at the follow-up ( g = 0.55). In particular, MBIs demonstrated to highly reduce stress ( g = 1.07) and to improve depression and anxiety symptoms with a moderate to large effect at postintervention ( g = 0.77 and g = 0.63, respectively). Conclusions: MBIs represent a valid and effective mind-body intervention to improve the well-being of patients with MS. Further studies should investigate which components of MBIs could be more beneficial for patients with progressive MS. PROSPERO registration : CRD42018099704. Abstract : Supplemental digital content is available in the text.